B cell epitopes on infliximab identified by oligopeptide microarray with unprocessed patient sera. Issue 1 (December 2015) - Homann, Arne; Röckendorf, Niels; Kromminga, Arno; Frey, Andreas; Jappe, Uta
Abstract Background Autoimmune diseases like rheumatoid arthritis and inflammatory bowel disease are treated with TNF-alpha-blocking antibodies such as infliximab and adalimumab. A common side effect of therapeutic antibodies is the induction of anti-drug antibodies, which may reduce therapeutic efficacy. Methods In order to reveal immunogenic epitopes on infliximab which are responsible for the adverse effects, sera from patients treated with infliximab were screened by ELISA for anti-infliximab antibodies. Sera containing high levels of anti-drug-antibodies (>1.25 µg/ml) were analyzed in an oligopeptide microarray system containing immobilized 15-meric oligopeptides from the infliximab amino acid sequence. Immunogenic infliximab IgG-epitopes were identified by infrared fluorescence scanning and comparison of infliximab-treated patients versus untreated controls. Results Six relevant epitopes on infliximab were recognized by the majority of all patient sera: 4 in the variable and 2 in the constant region. Three of the epitopes in the variable region are located in the TNF-alpha binding region of infliximab. The fourth epitope of the variable part of infliximab is located close to the TNF-alpha binding region and contains an N-glycosylation sequon. The sera positive for anti-infliximab antibodies do not contain antibodies against adalimumab as determined by ELISA. Thus, there is no infliximab–adalimumab cross-reactivity as determined by these systems. Conclusions Our data shall contribute to a knowledge-based recommendation for a potentially necessary therapy switch from infliximab to another type of TNF-alpha-blocker. The characterization of immunogenic epitopes on therapeutic monoclonal antibodies using unprocessed patient sera shall lead to direct translational aspects for the development of less immunogenic therapeutic antibodies. Patients benefit from less adverse events and longer lasting drug effects.